(3JhKjb YQi GdEjeGf aj JaVjd MHjH GdQMefs - (3GHf GdHGQRj , gHI Gddg Hf YHO GdQMje Hf EHQGgje, TQa GdOjf CHhGdbGSe,J (B738 (3g` s ((3CMeO Hf eMeO GdcYci GdHQgGfi s)
(3ChdgG (B:s
(3GdMeO ddg Pi GdYRI hGdSdWGf hGdfYeI hGdEeJfGf s
(3BNQgG (B:s
(3hfSCd Gddg QVi Gddg hQVi QShdg Udi Gddg Ydjg hSde YfG Ydi GdOhGe Bejf s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B73 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B139s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B101 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B133 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs